1999
DOI: 10.1016/s0378-1097(98)00605-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of host cell tyrosine phosphorylation in the invasion of HEp-2 cells by Bartonella bacilliformis

Abstract: We have provided evidence that exposure of human cells to protein kinase inhibitors results in decreased invasion of these cells by Bartonella bacilliformis in a dose-dependent manner. Preincubation of human laryngeal epithelial cells in the presence of genistein, a tyrosine protein kinase inhibitor, decreased the invasion of these cells by B. bacilliformis significantly. Further, exposure of normal human umbilical vein endothelial cells to staurosporine, a potent inhibitor of protein kinase C and some tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Early work on B. bacilliformis indicated that the bacterium is able to attach to and invade both human fibroblasts and epithelial cells (Hill et al, 1992). Moreover, it was shown that genistein, a tyrosine kinase inhibitor, decreased the invasion of the epithelial cells by B. bacilliformis (Williams-Bouyer & Hill, 1999), which indicate that the cells were actively engaged in the invasion process. Moreover, it was shown that genistein, a tyrosine kinase inhibitor, decreased the invasion of the epithelial cells by B. bacilliformis (Williams-Bouyer & Hill, 1999), which indicate that the cells were actively engaged in the invasion process.…”
Section: Interactions With Fibroblasts and Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early work on B. bacilliformis indicated that the bacterium is able to attach to and invade both human fibroblasts and epithelial cells (Hill et al, 1992). Moreover, it was shown that genistein, a tyrosine kinase inhibitor, decreased the invasion of the epithelial cells by B. bacilliformis (Williams-Bouyer & Hill, 1999), which indicate that the cells were actively engaged in the invasion process. Moreover, it was shown that genistein, a tyrosine kinase inhibitor, decreased the invasion of the epithelial cells by B. bacilliformis (Williams-Bouyer & Hill, 1999), which indicate that the cells were actively engaged in the invasion process.…”
Section: Interactions With Fibroblasts and Epithelial Cellsmentioning
confidence: 99%
“…The process appeared to require actin remodeling because cytochalasin D, a cell-permeable inhibitor of actin polymerization, inhibited the invasion (Hill et al, 1992). Interestingly, exposure of epithelial cell monolayers to anti-a5 and anti-b1 integrin monoclonal antibodies decreased the invasion of the cells by B. bacilliformis, suggesting a possible role of a5b1integrin (fibronectin receptor) in the bacterial uptake (Williams-Bouyer & Hill, 1999). Interestingly, exposure of epithelial cell monolayers to anti-a5 and anti-b1 integrin monoclonal antibodies decreased the invasion of the cells by B. bacilliformis, suggesting a possible role of a5b1integrin (fibronectin receptor) in the bacterial uptake (Williams-Bouyer & Hill, 1999).…”
Section: Interactions With Fibroblasts and Epithelial Cellsmentioning
confidence: 99%
“…The entry of B. bacilliformis was found to be fully or partially dependent on the activation of the small GTPases Rho, Rac, and Cdc42, on an altered pattern of tyrosine phosphorylation, and on ␣5␤1-integrins. Furthermore, the invasion process was dependent on a bacterial surface protein and involved actin rearrangements that manifested, during the course of intracellular persistence, as a massive formation of stress fibers anchored to focal adhesions (182,428,439). Interestingly, the intracellular vacuoles colonized by this species were shown to be associated with the Golgi complex, whose functions the pathogen could possibly manipulate in its favor, although intracellular replication has not been demonstrated (429,430).…”
Section: The Primary Nichementioning
confidence: 99%
“…More recent studies have identified some of the specific mammalian proteins that promote uptake, and a common feature is involvement in signaling pathways regulating actin polymerization or cytoskeletal architecture (16). The induction of tyrosine phosphorylation of host cell proteins by several pathogens has been reported (4,8,31). Since protein kinases play a major role in eukaryotic cells in transducing extra cellular signals, involvement of these enzymes and protein phosphorylation in the invasion of host cells by C. jejuni is of interest.…”
mentioning
confidence: 99%